The Role of Plant-Based Diets and Personalized Nutrition in Endometriosis Management: A Review - Marijana Matek Sarić; Tamara Sorić; Ana Sarić; Emili Marušić; Miran Čoklo; Mladen Mavar; Marija Ljubičić; Nataša Lisica Šikić (Medicina)
Endometriosis is a chronic, estrogen-dependent inflammatory condition that affects multiple organ systems and significantly impairs the quality of life in women of reproductive age. While conventional hormonal therapies may alleviate symptoms of endometriosis, they are also frequently associated with intolerable side effects. As a result, there is growing interest in complementary, non-invasive strategies to support long-term disease management. This review explores the potential of plant-based diets and personalized nutrition as adjunctive approaches in endometriosis care. Plant-based dietary patterns, which are rich in antioxidants, phytochemicals, dietary fiber, and essential micronutrients, have been shown to reduce systemic inflammation, modulate estrogen activity, and alleviate pelvic pain. Additionally, the use of medicinal plants, such as curcumin and ginger, has demonstrated anti-inflammatory and anti-proliferative effects in preclinical studies. Moreover, identifying and addressing individual food sensitivities, particularly to gluten, dairy, or fermentable oligosaccharides, disaccharides, monosaccharides, and polyols, may improve gastrointestinal and inflammatory symptoms in susceptible individuals. Future research should focus on high-quality clinical trials and integrative care models to evaluate the long-term efficacy, safety, and sustainability of these individualized nutritional interventions in the holistic management of endometriosis.